PENGARUH KONSELING GIZI TERHADAP ASUPAN NATRIUM PASIEN HIPERTENSI DIWILAYAH KERJA PUSKESMAS RURUKAN KOTA TOMOHON - Anggreni Makarawung; Nita R. Momongan; Henry S. Imbar (Jurnal GIZIDO, 2016)
Hypertension including disease can not be cured but can be controlled through routinehealth controls, a diet low in salt and consume regularly to reduce the risk of cardiovascularcomplications and other organs that exist in the patient. Salt is a critical role in thepathogenesis of hypertension. Table salt contains 40% sodium and 60% chloride. Nutritionalcounseling can assist patients in dealing with health issues. Changes in behavior will occur ifthe client receives knowledge so that clients can understand his state of health then theclient can take the correct attitude and action that has been agreed counselors to deal withtheir health problems.This type of research is the design of pre experiment with one group pretest posttestapproach, a population of 234 and the number of samples obtained from the calculationLemesshow (1997) a number of 40 samples. Wilcoxon test results before and after thesodium intake of nutritional counseling obtained significant value (0.000) <α (0:05) with anaverage intake of sodium respondents generally before and after counseling has decreasedfrom 3067 mg and 1490 mg after counseling.There are differences in sodium intake in hypertensive patients before and after nutritioncounseling. Prior to nutritional counseling patient sodium intake more than the recommendeddaily sodium intake, and nutritional counseling after the patient had begun to reduce eatingfoods that contain high sodium